Legal Protection for Consumers through the Politics of Dumping in Online Buying and Selling According to Law Number 8 of 1999 Concerning Consumer Protection - Ernawan, Didik; Sukresno, Sukresno (Jurnal Indonesia Sosial Sains, 2025)
The rapid advancement of technology has transformed commercial transactions, enabling consumers to access goods online more easily. However, this convenience has also made consumers increasingly vulnerable to misleading marketing practices, particularly in discount-based sales (obral). This study aims to analyze the legal protection afforded to consumers under Indonesian Law No. 8 of 1999 on Consumer Protection, focusing on deceptive practices in discount sales through online platforms. Utilizing a non-doctrinal legal research method, this study integrates statutory analysis with real-world consumer behavior and marketing phenomena. Data were collected through literature review and legal document analysis, focusing on primary legal materials such as the Indonesian Civil Code and relevant consumer protection laws. The findings reveal that despite clear regulations, particularly Article 11 letter (f) of Law No. 8/1999, many businesses continue to violate legal norms by using misleading discount claims, often resulting in consumer losses. The study highlights a lack of effective enforcement and public legal awareness as contributing factors to these recurring violations. It also emphasizes the urgent need for stronger regulatory supervision and educational initiatives to empower consumers. The implications of this research point to the necessity of integrating legal norms with ethical business practices to ensure a fair, transparent, and just digital marketplace. Recommendations include the enforcement of stricter penalties for violations and the promotion of legal literacy among consumers.